Epidemiology of tuberculosis in Chongqing, China: a secular trend from 1992 to 2015 - Bo Wu (Nature Portfolio, 2017)
Abstract Chongqing is a southwest city of China with high tuberculosis (TB) burden. An observational retrospective study has been performed based on routine TB surveillance data in Chongqing from 1992 to 2015. The TB notification rate has declined to 70.8 cases per 100,000 population from the peak of 106 cases per 100,000 in 2005. The TB notification rate in population over-65 years has become the highest among all-ages population since 2010. The average proportion of farmers in all notified cases from 2008 to 2015 was 62.5%, and the notification rate of farmers has become the highest among all occupations since 2011. The TB notification showed a regional disparity in Chongqing. Despite the improvement achieved since 1992, the TB control efforts has been threatened by new challenges such as the demographic shift towards an aging population, the prevalence of MDR-TB and TB/HIV co-infection, and the regional disparity of TB notification. More effective interventions should be implemented. Our study can serve as a guidance for the future development of TB control in Chongqing, and we believe it has general relevance to TB control in other regions with similar situations.